OPTIMIZATION DESIGN OF ARC TRUSS STRUCTURE BASED ON IMPROVED COOPERATION SEARCH ALGORITHM - LIU Ling; JIANG QuanXin (Jixie qiangdu)
Arc truss is a kind of basic structure commonly used in national economic construction, which has the advantages of light weight, long span and so on. In order to obtain the optimal solution of building are truss quickly and accurately, an improved cooperative search algorithm based on communication speech strategy is proposed. The performance of the improved cooperative search algorithm is verified by typical examples of 3-bar truss and 18 bar truss. The results show that the improved cooperative search algorithm has good convergence speed and robustness. Based on this, the improved cooperative search algorithm is used to optimize the design of building arc truss. The results show that after 46 iterations, the mass of arc truss is reduced from the initial 1 468. 51 kg to 1 284.85 kg, which is 12.51% lower than the initial value. The improved cooperative search algorithm is an optimization algorithm, which provides an efficient algorithm basis for practical engineering optimization problems.